Anterior insula degeneration in frontotemporal dementia - Seeley, William W. (Springer-Verlag, 2010)
The human anterior insula is anatomically and functionally heterogeneous, containing key nodes within distributed speech–language and viscero-autonomic/social–emotional networks. The frontotemporal dementias selectively target these large-scale systems, leading to at least three distinct clinical syndromes. Examining these disorders, researchers have begun to dissect functions which rely on specific insular nodes and networks. In the behavioral variant of frontotemporal dementia, early-stage frontoinsular degeneration begets progressive “Salience Network” breakdown that leaves patients unable to model the emotional impact of their own actions or inactions. Ongoing studies seek to clarify local microcircuit- and cellular-level factors that confer selective frontoinsular vulnerability. The search for frontotemporal dementia treatments will depend on a rich understanding of insular biology and could help clarify specialized human language, social, and emotional functions.